Multicolor flow cytometry and nanoparticle tracking analysis of extracellular vesicles in the plasma of normal pregnant and pre-eclamptic women. - Dragovic, R; Southcombe, J; Tannetta, D; Redman, C; Sargent, I (2013)
Excessive release of syncytiotrophoblast extracellular vesicles (STBMs) from the placenta into the maternal circulation may contribute to the systemic inflammation that is characteristic of pre-eclampsia (PE). Other intravascular cells types (platelets, leukocytes, red blood cells [RBCs], and endothelium) may also be activated and release extracellular vesicles (EVs). We developed a multicolor flow cytometry antibody panel to enumerate and phenotype STBMs in relation to other EVs in plasma from nonpregnant (NonP) and normal pregnant (NormP) women, and women with late-onset PE. Nanoparticle tracking analysis (NTA) was used to determine EV size and concentration. In vitro-derived STBMs and EVs from platelets, leukocytes, RBCs, and endothelial cells were examined to select suitable antibodies to analyze the corresponding plasma EVs. Flow cytometry analysis of plasma from NonP, NormP, and PE showed that STBMs comprised the smallest group of circulating EVs, whereas most were derived from platelets. The next most abundant group comprised unidentified orphan EVs (which did not label with any of the antibodies in the panel), followed by EVs from RBCs and leukocytes. NTA showed that the total number of EVs in plasma was significantly elevated in NormP and late-onset PE women compared to NonP controls, and that EVs were smaller in size. In general, EVs were elevated in pregnancy plasma apart from platelet EVs, which were reduced. These studies did not show any differences in EVs between NormP and PE, probably because late-onset PE was studied.